If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(1 + 5n) = -2(1 + 8n) (1 * -2 + 5n * -2) = -2(1 + 8n) (-2 + -10n) = -2(1 + 8n) -2 + -10n = (1 * -2 + 8n * -2) -2 + -10n = (-2 + -16n) Add '2' to each side of the equation. -2 + 2 + -10n = -2 + 2 + -16n Combine like terms: -2 + 2 = 0 0 + -10n = -2 + 2 + -16n -10n = -2 + 2 + -16n Combine like terms: -2 + 2 = 0 -10n = 0 + -16n -10n = -16n Solving -10n = -16n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '16n' to each side of the equation. -10n + 16n = -16n + 16n Combine like terms: -10n + 16n = 6n 6n = -16n + 16n Combine like terms: -16n + 16n = 0 6n = 0 Divide each side by '6'. n = 0 Simplifying n = 0
| 5x+233=3x+187 | | 3(4x-3)-(x+7)=5(10-x)+7 | | -6-3x=9x-8x | | 3(4x-3)-(x+7)=5(10-x)+2 | | 4.5f=47.25 | | 19-7a=-9 | | -4(k^2+3)+15=-85 | | -16=d | | -7(x+4)-43=3-39 | | -7x-3=4x+30 | | 5(3-6n)-2(1-3n)=-7n-4n | | -8=10-6 | | 2.5x-3.5=96.5 | | -4(x-7)=-12 | | n+130+150=480 | | 33d=924 | | 5(x+6)=60 | | 8x+4(4x-3)=24x-12 | | 6x+7(x-4)+12=-55 | | -8x-11=13 | | 1.3c=16.9 | | f(x)=5(x)+1 | | -2f+6=-10 | | -10y+5y=45 | | 4.2v=0.46666666667 | | 25.2+3y=12 | | 5.95+19p=15.83 | | 9x-(3x-8)=20 | | 42a-16=6a+8 | | 5.95+19=15.83 | | 6x+9-6x=3x+6x | | y-7=-4x-8 |